The Effectiveness of Zakat Distribution by Waqf Institution: Perspectives of Zakat Contributors in Kuching - Nur Constance, Wah; Norlina, Kadri; Muhammad Hafiz, Mohd Shukri; Nur Nadhira, Baharuddin; Shafinah, Rahim (2024)
Zakat institution is an integral part of the Islamic socio-economic system. In Malaysia. zakat administration is institutionalized as a state matter and therefore the respective state authorities are responsible for its promotion, collection and distribution. The sustainable growth and effectiveness of zakat as mechanism to uplift the spirit and standards of living of Muslims depends mainly on the clear, consistent and comprehensive understanding amongst both the donors and recipients. This study aims at identifying the contributors or known as the muzakkis level of satisfaction with the progress made by the waqf Institution and exploring the factors influencing their concerns relating to distribution of zakat funds in Sarawak. This research takes a qualitative approach, involving personal in-depth interviews. Findings from nine personal in-depth interviews found that the muzakkis viewed on zakat distribution in Kuching are at satisfactory level. Nevertheless, there a several critical aspects need to be improved such at the muzakkis engagement, technology savvy, stakeholders involvement in the consumer waqf institution policy maker. The findings from the research are expected to benefit waqf institution in designing their educational and outreach programs, while connecting to muzakkis through shared ideas.